Characterization and typification of small-scale goat production systems in the highlands of southeast Peru - Palomino Guerrera, Walter; Godoy Padilla, David; Huaripaucar Huancahuari, Joseen; Sessarego Dávila, Emmanuel; Trillo Zárate, Fritz; Cruz Luis, Juancarlos (Frontiers Media, 2024)
Articulo científico